1997
DOI: 10.1002/(sici)1096-8628(19971219)73:3<337::aid-ajmg21>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Application of transmission disequilibrium tests to nonsyndromic oral clefts: Including candidate genes and environmental exposures in the models

Abstract: Extensive epidemiological and genetic studies of the cause of oral clefts have demonstrated strong familial aggregation but have failed to yield definitive evidence of any single genetic mechanism. We used the transmission/disequilibrium test (TDT) to investigate the relationship between oral clefts and markers associated with five candidate genes by utilizing 160 parent-offspring trios. Conditional logistic regression models extended the TDT to include covariates as effect modifiers, thus permitting tests for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1
7

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 22 publications
6
98
1
7
Order By: Relevance
“…Consistent with this hypothesis, Tgf-b3 -/-knockout mice present with a developmental defect of the secondary palate (Proetzel et al 1995). In humans, however, evidence for any involvement of the TGFB3 gene in development of oral clefts has remained inconclusive, with reports of significant (Maestri et al 1997;Lidral et al 1998;Romitti et al 1999;Mitchell et al 2001;Sato et al 2001;Beaty et al 2002;Scapoli et al 2002;Jugessur et al 2003;Kim et al 2003;Slayton et al 2003;Vieira et al 2003;Suzuki et al 2004) as well as negative (Lidral et al 1997;Tanabe et al 2000;Beaty et al 2001;MorkĆ«nienĂ© et al 2007) associations among different populations with nonsyndromic orofacial clefts. In this study, we investigated whether the results of Ichikawa et al (2006), who conducted the most comprehensive study of TGFB3 to date, were also apparent in CL/P families of central European descent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, Tgf-b3 -/-knockout mice present with a developmental defect of the secondary palate (Proetzel et al 1995). In humans, however, evidence for any involvement of the TGFB3 gene in development of oral clefts has remained inconclusive, with reports of significant (Maestri et al 1997;Lidral et al 1998;Romitti et al 1999;Mitchell et al 2001;Sato et al 2001;Beaty et al 2002;Scapoli et al 2002;Jugessur et al 2003;Kim et al 2003;Slayton et al 2003;Vieira et al 2003;Suzuki et al 2004) as well as negative (Lidral et al 1997;Tanabe et al 2000;Beaty et al 2001;MorkĆ«nienĂ© et al 2007) associations among different populations with nonsyndromic orofacial clefts. In this study, we investigated whether the results of Ichikawa et al (2006), who conducted the most comprehensive study of TGFB3 to date, were also apparent in CL/P families of central European descent.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a genetic deletion of Tgf-b3 (-/-) present with either complete cleft palate or severe partial cleft palate (Kaartinen et al 1995;Proetzel et al 1995). Genetic association studies in humans of different ethnicities suggest TGFB3 may be involved in the formation of orofacial clefts (Maestri et al 1997;Lidral et al 1998;Romitti et al 1999;Mitchell et al 2001;Sato et al 2001;Beaty et al 2002;Scapoli et al 2002;Jugessur et al 2003;Kim et al 2003;Slayton et al 2003;Vieira et al 2003;Suzuki et al 2004), although negative studies have also been reported (Lidral et al 1997;Tanabe et al 2000;Beaty et al 2001;MorkĆ«nienĂ© et al 2007). Until recently, most studies used a CA repeat located 61.215 bp upstream from translation starting point of TGFB3 as well as a VNTR marker in the 5 0 untranslated region (UTR) (D at -21083 to -21086 (AGAGGG repeat)) and with X5.1 a T [ C substitution [ref.…”
Section: Introductionmentioning
confidence: 99%
“…Tests of gene-environment interaction have also been proposed in the family-based framework (Khoury & Flanders, 1996;Maestri et al 1997;Schaid, 1999;Waldman et al 1999;Witte et al 1999;Lunetta et al 2000;Umbach & Weinberg, 2000). As discussed by Umbach & Weinberg (2000), a number of these methods do not guarantee protection from population admixture.…”
Section: Discussionmentioning
confidence: 99%
“…The second cause of potentially spurious results is the nonindependence of disease allele transmissions between heterozygous parents under the null hypothesis of no interaction. As Umbach & Weinberg (2000) state, such bias may arise in any test of gene-environment interaction that is based on the counting of transmissions from heterozygous parents, including the logistic regression approaches of Maestri et al (1997) and Waldman et al (1999). While the method of Lunetta et al (2000) is robust to these potential pitfalls, the null hypotheses for the tests assume that there is no interaction as well as no main effects of the gene or environmental exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, the first reports emerged on the association between increased frequency of CL/P and the occurrence of genetic variations in the locus for transforming growth factors alpha and beta (TGFα/TGFÎČ) (Ardinger et al, 1989;Maestri, et al, 1997;Shiang et al, 1993). Genetic analysis and specific tissue expression studies support the theory that specific variants of alleles in the TGFα gene participate actively in the craniofacial development mechanism (Shiang et al, 1993).…”
Section: Evidence Of Association Between Oral Hormones and Orofacial mentioning
confidence: 99%